Yayasan UMP receives RM470,648 from MUIP for zakat distribution and disaster relief - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA Besar, 20 September 2022 - Yayasan Universiti Malaysia Pahang received RM470,648.75 from the Pahang Islamic Religious and Malay Customs Council (MUIP), including RM220,648.75 in zakat fund assistance, Malaysian Family Eldest Student Development Programme (Sulung Scholarship) amounting to RM200,000.00 and RM50,000.00 in Disaster Relief.